RESISTENSI PEREMPUAN BALI PADA SEKTOR INDUSTRI KREATIF DI DESA PAKSEBALI, KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Widiastiti, Anak Agung Istri Putera (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies), 2012)
Gender’s of distinguished male and female as a resultof development social construction in society effect tosubordination female. That is seems in sector developmentcreative industry at Paksebali’s village. Claim job willhappen only for a male, meanwhile female job result arequalify tend on by its character helping their husband jobonly. That is bring on unsatisfactory among female worker,it has been impacted going on resistensi’s action. Farther,this research intended to know the forms, understanding ofmotivate factors, and to understand impact and interpretingthe meaning of resistensi’s Bali female on sector creativeindustry at Paksebali’s village.